2013
DOI: 10.1016/j.amepre.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Exposure to Point-of-Sale Tobacco

Abstract: Background Little is known about the factors that drive the association between point-of-sale marketing and behavior, because methods that directly link individual-level use outcomes to real-world point-of-sale exposure are only now beginning to be developed. Purpose Daily outcomes during smoking cessation were examined as a function of both real-time geospatial exposure to point-of-sale tobacco (POST) and subjective craving to smoke. Methods Continuous individual geospatial location data collected over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 38 publications
0
63
0
Order By: Relevance
“…The current outlet environment may be a critical component in promoting young adult tobacco product initiation. The pervasive availability of a multiplying array of tobacco products in local retail outlets globally, coupled with a growing body of evidence on the impact of outlets on smoking behavior, [10][11][12][13][14][16][17][18] suggests that the current outlet environment may be a contributing factor in promoting adult tobacco product experimentation and initiation. Licensing and zoning policies to restrict tobacco outlet density may be instrumental in reducing tobacco use initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current outlet environment may be a critical component in promoting young adult tobacco product initiation. The pervasive availability of a multiplying array of tobacco products in local retail outlets globally, coupled with a growing body of evidence on the impact of outlets on smoking behavior, [10][11][12][13][14][16][17][18] suggests that the current outlet environment may be a contributing factor in promoting adult tobacco product experimentation and initiation. Licensing and zoning policies to restrict tobacco outlet density may be instrumental in reducing tobacco use initiation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent years have seen a growing interest in reducing tobacco availability via retail outlets, 9 along with growing evidence that the distribution of outlets may impact tobacco use behavior. Studies have found that outlet density is associated with increased cigarette smoking among youth, [10][11][12][13][14] while outlet proximity [15][16][17][18] is associated with reduced smoking cessation among adults. However, evidence examining the impact of outlets on cigarette smoking or use of other tobacco products among young adults is scarce.…”
Section: Original Investigationmentioning
confidence: 99%
“…Having sensitive and reliable approaches that encourage accurate self-reporting about tobacco use is critical to appropriately evaluating interventions. Ecological Momentary Assessment devices can be programmed to more precisely and efficiently capture poly-product use patterns in near real time as well as simultaneously evaluate the social and contextual factors driving use (Kirchner et al 2013;Setodji et al 2013;Thrul et al 2014).…”
Section: Evaluating Prevescalation Interventionsmentioning
confidence: 99%
“…There is great potential of mHealth technology, yet it is imperative that we first address these ethical considerations to ensure that we capitalise on the possible benefits of these technologies while minimising the potential risks to the users. BinDhim et al, 2014;Borland et al, 2013;Bricker et al, 2014;Buller et al, 2014;Haug et al, 2014;Hertzberg et al, 2013;Kirchner et al, 2013;Meredith et al, 2014;V. Patel, Nowostawski, Thomson, Wilson, & Medlin, 2013;Ploderer et al, 2014;Reitzel et al, 2014; Whittaker, 2011) Alcohol 12 (34.3%) (Bendtsen & Bendtsen, 2014;Dulin et al, 2014;Gajecki et al, 2014;Gamito et al, 2014;Haug et al, 2014;Kauer, Reid, Sanci, & Patton, 2009;Matsumura, Yamakoshi, & Ida, 2009;McTavish et al, 2012;Renner, 2012;Yu et al, 2012) Heroin 2 (5.7%) Epstein et al, 2009) Cocaine 1 (2.9%) (Freedman, Lester, McNamara, Milby, & Schumacher, 2006) General 3 (8.6%) (Campling, 2011;Ingersoll et al, 2014; Bendtsen & Bendtsen, 2014;BinDhim et al, 2014;Borland et al, 2013;Bricker et al, 2014;Buller et al, 2014;Dulin et al, 2014;Hasin et al, 2014;Haug et al, 2014;Ingersoll et al, 2014;Ploderer et al, 2014;…”
Section: Discussionmentioning
confidence: 99%
“…Twenty apps provided users with an element of control over the utility of the app. For example, a number of apps sought to maintain user privacy by providing the participant with the ability to turn off alerts at certain times (Keoleian, Stalcup, Polcin, Brown, & Galloway, 2013;Kirchner et al, 2013;McTavish et al, 2012;. One application allowed the user to switch off location services when desired , potentially A c c e p t e d M a n u s c r i p t 8 reducing the amount of unnecessary data collected and the possibility of a third-party identifying the user through data profiling (Gasson et al, 2011).…”
Section: Privacymentioning
confidence: 99%